Hepatic Cirrhosis with Esophageal Varices: A Case Report - Minanti, Nanda Anessa; Yusri Dianne Jurnalis (HM Publisher, 2024)
Background: In adults, portal hypertension is generally caused by hepatic cirrhosis, whereas in children it is more commonly caused by extrahepatic abnormalities with normal liver function. Portal hypertension causes hemodynamic abnormalities. Gastrointestinal bleeding is the most severe clinical manifestation of portal hypertension in both children and adults. Pathogenetically, increased pressure in the portal vein can be caused by increased vascular resistance and increased portal blood flow. The site of obstruction can be prehepatic (portal vein obstruction), intrahepatic (presinusoidal: eg congenital hepatic fibrosis; para sinusoidal: cirrhosis, hepatotoxic drug therapy, vitamin A hepatotoxicity; post sinusoidal: venocclusive disease) and/or post hepatic (Budd-Chiari syndrome, constrictive pericarditis). Case presentation: The study reports the results of observations of a case of a boy, FAA, aged 12 years and 2 months who came to the emergency room at Dr. M. Djamil General Hospital Padang with the main complaint of hematemesis and splenomegaly from physical examination. Non cirrhotic portal fibrosis is a cause that is not uncommon in the population in the early second decade of life. Some children with non-cirrhotic portal fibrosis as adults can end up with end stage liver disease. Conclusion: Patients with noncirrhotic or cirrhotic portal hypertension can be assessed using the Child Pugh instrument as an instrument that is still used to determine the survival rate if patients with portal hypertension.